Implementasi Manajemen Perpustakaan - Syah, Widdy Yos Firman; Ripai, Ahmad -; -, Subur - (JIEM (Journal of Islamic Education Management), 2022)
Library is one of educational institutions  component and also one of the most important learning resources, that's why, every school must have a library and organize it accordance with the national library standards and library management is needed. The title of this research was The Implementation of Library Management in State Madrasah Tsanawiyah 3 of Cirebon Regency. The purpose of this research was to find out how the implementation of Library Management in State Madrasah Tsanawiyah 3 of Cirebon Regency is. The researcher used descriptive qualitative method in this research. The data collection technique was observation, interview and documentation techniques. Data analysis techniques used data reduction, data presentation and conclusions. The result of the research was indicated that library management has implemented a management function, namely (POAC) Planning, Organizing, Actuating, Controlling. Although there were some things that must be addressed, such as facilities and infrastructures, human resources, library materials, operational costs and library services to be even better.Keywords: Implementation, Management, Library  Perpustakaan merupakan salah satu komponen dalam suatu lembaga pendidikan  perpustakaan juga merupakan salah satu sumber belajar yang sangat penting, untuk itu setiap sekolah harus memiliki dan menyelenggarakan perpustakaan yang sesuai dengan standar nasional perpustakaan, perlu adanya manajemen. Skripsi ini berjudul Implementasi Manajemen Perpustakaan di MTs Negeri 3 Kabupaten Cirebon. tujuan adanya penelitian ini tentu untuk mengetahui bagaimana Pengelolaan Perpustakaan di MTs Negeri 3 Kabupaten Cirebon. Metode yang digunakan dalam penelitian ini yaitu metode kualitatif deskriptif. Teknik yang digunakan dalam pengumpulan datanya yaitu teknik observasi, wawancara dan dokumentasi.  Teknik analisis data menggunakan reduksi data, penyajian data, penarikan kesimpulan. Hasil penelitian yang menunjukan bahwa pengelolaan perpustakaan sudah menerapkan fungsi manajemen yaitu (POAC) Planning, Organizing, Actuating, Controlling. Meskipun masih ada beberapa hal yang harus dibenahi, seperti sarana dan prasarana, sumber daya manusia, bahan pustaka, biaya operasional dan pelayanan perpustakaannya agar lebih baik lagi.Kata Kunci : Implementasi, Manajemen, Perpustakaan